علاقة بعض الأساليب المعرفية بصعوبات القراءة - جاري, البشير; جاري, نعيمة (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية للكشف عن دلالة الفروق بين التلاميذ العاديين والتلاميذ ذوي صعوبات القراءة في الأسلوبين المعرفيين: التروي مقابل الاندفاع والاستقلال عن المجال مقابل الاعتماد. اعتمدت الدراسة على المنهج الوصفي المقارن وطبقت على عينة قوامها 44 تلميذا منهم 22 تلميذا من ذوي صعوبات القراءة متمدرسين بأقسام السنة خامسة ابتدائي ببعض إبتدائيات ولاية الوادي. تم اختيار العينة بطريقة قصدية لذوي صعوبات القراءة أما العاديين فقد اختيروا بطريقة عشوائية، ولجمع بيانات الدراسة تم استخدام المقاييس التالية: اختبار الذكاء واختبار الكلمات وشبه الكلمات لتشخيص ذوي صعوبات القراءة واختباري تزاوج الأشكال المألوفة و الأشكال المتضمنة. بعد معالجة بيانات الدراسة إلى النتائج التالية: ــ توجد فروق في الأسلوب المعرفي(التروي مقابل الاندفاع)من خلال زمن الاستجابة وعدد الأخطاء بين متوسطي درجات التلاميذ العاديين وذوي صعوبات القراءة. ــ توجد فروق في الأسلوب المعرفي(الاستقلال مقابل الاعتماد بين متوسطي درجات التلاميذ العاديين وذوي صعوبات القراءة. Abstract: The current study aimed to reveal the significance of the differences between normal students and students with reading difficulties in the two cognitive styles: deliberation versus impulsiveness and independence from the field versus dependence. The study relied on the comparative descriptive approach and was applied to a sample of 44 students, including 22 students with reading difficulties, studying in the sections of the fifth year of primary school in some elementary schools in El-Oued. The sample was selected using a comprehensive enumeration method for people with reading difficulties, while those with normal reading difficulties were chosen randomly. To collect the study data, the following measures were used: intelligence test, word-like test for diagnosing people with reading difficulties, and pairing tests of familiar shapes and included shapes. After processing the study data, the following results were obtained: There are differences in the cognitive style (reflective versus impulsive) through the response time and the number of errors between the mean scores of ordinary students and those with reading difficulties. And There are differences in the cognitive style (independence versus dependence) between the mean scores of ordinary students and those with reading difficulties.
دراسة وصفية مقارنة لدى تلاميذ السنة الخامسة ابتدائي بولاية الوادي
مقال
Keywords: الأساليب المعرفية ; صعبات القراءة; Cognitive styles; reading difficulties